Effects of PM, TVOCs and comfort parameters on indoor air quality of residences with young children. (March 2019) - Stamatelopoulou, A.; Asimakopoulos, D.N.; Maggos, T.
Abstract: Indoor air pollution has been implicated in an array of detrimental health effects. Although infants and young children spend most of their day inside their residence, information regarding their exposure to indoor pollutants is still limited. Therefore, the objectives of this study were: a) to characterize the concentrations of particulate matter (PM) and total volatile organic compounds (TVOCs) that young children are exposed to; b) to define comfort parameters for living rooms and children's bedrooms; c) to identify the determinants of indoor PM and TVOC concentrations; and d) to examine how the socioeconomic status of inhabitants and their daily activities affect diurnal variations in these indoor pollutants. In this context, a study of PM, TVOCs, and comfort parameters was conducted in Athens, Greece, in residences with young children below three years of age. Sampling campaigns were conducted over a 6–7 day period using real time monitoring. The mean indoor PM1, PM2.5, and PM10 concentrations were 8.1, 10.6, and 20.9 μg/m 3, respectively. Mean concentrations of TVOCs ranged between 24 μg/m 3 and 890 μg/m 3, indicating high variance across the studied dwellings. Carbon dioxide (CO2 ) levels exceeded the reference value of 1000 ppm in several residences, especially in children's bedrooms, while air exchange rates (AERs) were found to be lower than 0.5 h −1 in all the studied houses. The results indicated that both PM and TVOC concentrations were mainly related to the activities of the study participants inside their residences. Highlights: PM, TVOCs and comfort parameters were measured in 13 residences, where young children below 3 years old live. PM and TVOC concentration levels are mainly related to the activities of the participants inside their residences. Smoking was found to contribute to high TVOC and PM levels, especially in the fine fraction. Cooking and especially frying was found to contribute to elevated PM concentrations. The pollutants concentrations can be characterized as concerning regarding their possible implications on children's health.